2020
DOI: 10.3389/fneur.2020.557233
|View full text |Cite|
|
Sign up to set email alerts
|

Middle Meningeal Artery Embolization for Chronic Subdural Hematoma

Abstract: Chronic subdural hematoma (cSDH) is a common disease process associated with significant morbidity that occurs most often in elderly patients. Asymptomatic patients are typically treated conservatively, with surgical intervention reserved for patients with symptomatic and/or large hematomas that cause brain compression. However, conservatively managed cSDH cases frequently progress, and surgical evacuation of cSDH is associated with high rates of complication and recurrence. Recently, successful treatment of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 52 publications
0
61
0
Order By: Relevance
“…Embolization was conducted either in isolation, in combination with surgical intervention or with drugs. Also, different embolization agents, extent of penetration, patient selection, timing of embolization and number of MMA branches embolized were used in the different studies (Catapano et al, 2020(Catapano et al, , 2021a. Moreover, symptoms and neurological deficits from CSDH arise most often due to the mass effect of the subdural collection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embolization was conducted either in isolation, in combination with surgical intervention or with drugs. Also, different embolization agents, extent of penetration, patient selection, timing of embolization and number of MMA branches embolized were used in the different studies (Catapano et al, 2020(Catapano et al, , 2021a. Moreover, symptoms and neurological deficits from CSDH arise most often due to the mass effect of the subdural collection.…”
Section: Discussionmentioning
confidence: 99%
“…Rupture of these neo-vessels may further enlarge the hematoma ( Takizawa et al, 2016 ). Hence, eliminating the blood supply to the outer neomembrane by embolization of the MMA (eMMA) has been proposed as a minimally invasive treatment for CSDH ( Ban et al, 2018 ; Catapano et al, 2020 , 2021a , 2021b ). And several systematic reviews and a meta-analysis have shown promising results with MMA embolization, including low rates of complication and recurrence ( Haldrup et al, 2020 ; Ironside et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 , 5 ] Although surgical evacuation through burr holes or conventional craniotomy remains the treatment of choice for large symptomatic CSDH, embolization of the middle meningeal artery (MMA) is emerging as an increasingly common treatment strategy. [ 3 , 12 ] Dural arteriovenous fistulas (DAVFs) are abnormal shunts between dural arteries and venous sinuses. Venous sinus thrombosis, prior surgery, and trauma[ 7 , 9 , 10 ] have all been implicated in DAVF formation, presumably through inflammatory and neoangiogenic-mediated recanalization of extant arteriovenous anastomoses.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no definite conclusion about the effect of propofol on the brain. Studies suggested that propofol can cause forgetting and even lead to impaired memory function [8]. However, there is also a view that propofol has no effect on the learning ability and memory function of experimental animals.…”
Section: Introductionmentioning
confidence: 99%